Factors associated with self-reported medical errors among undergraduate health science students in southern Ethiopia - Toitole, Kusse Koirita; Danaso, Fekade Tesfaye; Alto, Saron Assefa; Mohammed, Tofik; Dejene, Sisay; Boynito, Wanzahun Godana (Frontiers in Medicine, 2024)
Introduction Medical errors are not uncommon, but they are seldom reported. Patient safety practices are among the key areas for service improvement. This study aimed to assess factors associated with self-reported medical errors among undergraduate health science students in southern Ethiopia. Methods A facility-based cross-sectional study was conducted among health science students of Arba Minch University in 2018. The sample size was calculated using a single population proportion formula. A total of 287 medical students in their fourth year and above, nursing and midwifery students in their second year and above, and other health science students in their third year and above were included. Results The majority (82.1, 95%CI: 77.63–86.67) of the study participants had a ‘good’ knowledge score on patient safety. Approximately 62.5% (95%CI: 56.8–68.2) of the participants had a ‘favorable’ patient safety attitude. Only 38.6% (95%CI: 32.8–44.3) of the study participants had ‘good’ patient safety practices. At adjusted analysis, the practical attachment unit, having ever managed a patient independently, having ever witnessed harm to patients by colleagues or other healthcare workers, and having ever witnessed harm to a close friend or family member were statistically significantly associated with self-reported medical errors. Participants who were doing their practical clinical attachment in the surgical and obstetric units were three times more likely to self-report medical errors as compared to those practicing in the pediatrics, internal medicine, and other units (AOR = 2.72, 95%CI: 1.16–6.39.97). Students who had never managed a patient independently were less likely to self-report medical error (AOR = 0.24, 95%CI: 0.08–0.72). The odds of self-reporting medical errors were less among among participants who had not ever witnessed harm to patients by colleagues or other healthcare workers (AOR = 0.12, 95%CI: 0.05–0.29) and participants who had not ever witnessed harm to a close friend or family member (AOR = 0.36, 95%CI: 0.16–0.80). Conclusion One in five of the participants reported having harmed patients while practicing. Most of the students had good patient safety knowledge, while approximately two-thirds of the participants had a favorable attitude toward patient safety. Only 38.6% of the study participants had good patient safety practices. Having worked in surgical and obstetrics units, having managed a patient independently, and having witnessed harm to a patient were associated with self-reporting of medical errors.